ANALYSIS OF LOW PERFORMANCE OF THE BEKASI CITY LAND AGENCY IN LAND CERTIFICATION SERVICES - Viery Bramantio Widihutomo Putra; Budi Puspo Priyadi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Service performance is critical to the government and the community. This research aims to identify performance and factors that affect the performance of the land Office of Bekasi City in the soil certification service. Performance identification: using the dimensions of quality, quantity, timeliness, cost effectiveness, need for supervision, and interpersonal impact. The research method used is qualitative descriptive research with the focus of performance analysis research on community land certification services, and the local office of the city of Bekasi. Determination of informant using purposive sampling technique with informant: Head of service section of land and measurement land certification, staff of National Land Agency of Bekasi City, and people of Bekasi City who manage land certification in National Land Office of Bekasi City. Data used: Primary data and secondary data, using data collection techniques: Interviews, observations, and documentation. The data analysis techniques used is dominant analysis techniques through: data reduction, data display, and verification, by testing the validity of data using triangulation techniques. The conclusion is performance of the Organization in the Land Office of Bekasi City is still low and not optimal. As for the factors that affect it, there are still overlapping jobs, the lack of employees and the majority of active employees are already entering the elderly, the management information system applied is problematic, and there is still a facility The problematic. The advice that can be given is: the addition of the number of employees, coaching officers by Land Training Agency and the internal land office of Bekasi City, improvement of infrastructure facilities, conduct routine evaluation meetings, and tighten the supervision of budgets Keywords :